Оптимизация внутриблочных технологических процессов тепловой электростанции - Дуэль, М. А.; Канюк, Г. И.; Фурсова, Т. Н. (My University, 2014)
Рассмотрены вопросы оптимизации внутриблочных технологических процессов ТЭС для повышения качества и эффективности работы системы автоматического регулирования в реальных условиях эксплуатации энергоблока. Для решения оптимизационных задач проводится декомпозиция энергоблока как объекта управления. В качестве примера оптимизации подсистем автоматического управления энергоблока рассмотрена система оптимизации процесса горения в топке парогенератора ТЭС.

This scientific paper discusses the problems related to the optimization of the interblock technological processes that occur in thermal power stations. The purpose of the research is to improve the quality and efficiency of the operation of automatic control system in the real operation conditions of power units. To solve the optimization problem the decomposition of the power unit as a control object has been done. The optimization system of burning processes in the steam generator furnace of the thermal power station has been taken as an example for the optimization of the subsystems of automatic power unit control. The technoeconomic effect provided by the system introduction was assessed interms of an increase in the efficiency factor of the steam generator by (0,2 to 0,3) %. The obtained investigation data can be of interest for the specialists working for thermal powerstations. The design and implementation of optimal automatic control systems that are based on up-to-date technical tools and are used for technological energy production processes will provide positive influence on reliability and technoeconomic indices of those processes.
Optimization of the interblock processes that occur in thermal power stations
Keywords: системы автоматического регулирования; энергоблок; automatic regulation; control systems; technological processes; optimization; power unit